2017
DOI: 10.1534/genetics.116.193458
|View full text |Cite
|
Sign up to set email alerts
|

Traffic Through the Trans-Golgi Network and the Endosomal System Requires Collaboration Between Exomer and Clathrin Adaptors in Fission Yeast

Abstract: Despite its biological and medical relevance, traffic from the Golgi to the plasma membrane (PM) is one of the least understood steps of secretion. Exomer is a protein complex that mediates the trafficking of certain cargoes from the trans-Golgi network/early endosomes to the PM in budding yeast. Here, we show that in Schizosaccharomyces pombe the Cfr1 and Bch1 proteins constitute the simplest form of an exomer. Cfr1 co-immunoprecipitates with Assembly Polypeptide adaptor 1 (AP-1), AP-2, and Golgi-localized, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(49 citation statements)
references
References 66 publications
(118 reference statements)
4
37
0
8
Order By: Relevance
“…These findings are 118 consistent with exomer having a more general role in the organization of the TGN, 119 which has been proposed following the characterization of exomer-deficient mutants in 120 S. pombe (Hoya et al, 2017). 121…”
supporting
confidence: 68%
“…These findings are 118 consistent with exomer having a more general role in the organization of the TGN, 119 which has been proposed following the characterization of exomer-deficient mutants in 120 S. pombe (Hoya et al, 2017). 121…”
supporting
confidence: 68%
“…Notably, in S. cerevisiae , there are two forms of AP-1 which share the same large (Apl2 and Apl4) and small (Aps1) subunits, but distinct medium subunits (Apm1 or Apm2) that seem to confer differential cargo recognition and sorting (Valdivia et al, 2002; Renard et al, 2010; Whitfield et al, 2016). Additionally, in yeast, the AP-1 complex seems to co-operate with the exomer, a non-essential, fungal-specific heterotetrameric complex assembled at the trans-Golgi network, for the delivery of a distinct set of proteins to the plasma membrane (Hoya et al, 2017; Anton et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Other adaptors, some of which display similarity to AP subunits, like the GGAs, epsin-related proteins, or components of the exomer and retromer complexes are also critical for the sorting of specific cargoes (Bonifacino 2004; 2014; Robinson 2015; Spang 2015; Anton et al, 2018). Importantly, the various cargo sorting routes are often overlapping and might share common adaptors (Hoya et al, 2017). Among the major AP complexes (Bonifacino 2014; Nakatsu et al, 2014), AP-1 and AP-2, which in most cells work to propel vesicle formation through recruitment of clathrin, are the most critical for cell homeostasis and function (Robinson 2004; 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Previous work showed that trafficking from the endosome is regulated by the clathrin adaptor protein Apm1 (AP-1), which localizes to endosomes, and apm1∆ accumulates post-Golgi vesicles (Kita et al, 2004). The exomer complex, formed by Bch1 and Cfr1, which also localizes to endosomes, plays a more minor role, though apm1∆ exomer∆ mutants display enhanced defect in trafficking from the endosome (Hoya et al, 2017). Consistent with aberrant endosome organization, apm1∆ and apm1∆ exomer∆ triple mutants showed extensive D4H internal signal ( Fig 4D).…”
Section: Sterols Travel Between the Pm And Endosomes Independently Ofmentioning
confidence: 99%
“…Vesicular trafficking from the TGN to the PM relies on transport along actin cables, assembled by the formin For3 in fission yeast, and tethering at the PM by the exocyst complex (Bendezu and Martin, 2011;Feierbach et al, 2004;TerBush et al, 1996;Wang et al, 2002). Other complexes such as exomer or clathrin adaptors contribute to sorting from the TGN (Hoya et al, 2017;Wang et al, 2006). Our extended knowledge of protein trafficking contrasts sharply with that of sterol transport, which remains mostly unknown.…”
Section: Introductionmentioning
confidence: 99%